LINGUISTIC ANALYSIS OF NOUN GROUP SEMANTIC GROUP MODELING (Scientific journal of the Fergana State University, 2024)
In this article, the meaning groups of nouns are evaluated based on mathematical parameters. First, the scientists who conducted linguostatistical research on computer linguistics on Uzbek language materials are listed. This article serves to strengthen the scientific theory. Relying on the linguistic studies of linguists, the meaning groups of nouns were modeled nationally on the basis of deductive principles and analyzed in the linguistic direction. As a result of the analysis, a total of 37 models were developed for the meaning groups of nouns, which are divided into core models, transpositional models, transnominative models, structural models, macrosystem and microsystem models. The listed types of national models are explained. Tables were used effectively in writing the article. He tried to reveal the hierarchical relationship between the meaning groups of the noun group through the models. It is also revealed that one word belongs to different meaning groups through national models.